Maternal and neonatal bleeding complications in relation to peripartum management in women with Von Willebrand disease: A systematic review. (January 2020) - Punt, M.C.; Waning, M.L.; Mauser-Bunschoten, E.P.; Kruip, M.J.H.A.; Eikenboom, J.; Nieuwenhuizen, L.; Makelburg, A.B.U.; Driessens, M.H.E.; Duvekot, J.J.; Peters, M.; Middeldorp, J.M.; Bloemenkamp, K.W.M.; et al.
Abstract: Women with Von Willebrand disease (VWD) have an increased risk of developing postpartum hemorrhage (PPH). Our aim is to evaluate peripartum management strategies in relation to maternal and neonatal bleeding complications in VWD. Electronic databases were searched up to January 2019. Seventy-one case-reports and -series and 16 cohort studies were selected, including 811 deliveries. Cohort studies reported primary PPH in 32% and secondary PPH in 13% of the women. The overall primary PPH incidence in the individual patient data was 34%, similar between women who received prophylactic treatment to prevent PPH and those who didn't. Neonatal bleeding events were reported in 4.6% of deliveries. Overall, the available evidence on peripartum management in women with VWD was of low quality. The ongoing high risk for PPH is evident, despite prophylactic treatment, as well as the need for higher quality evidence from larger prospective cohort studies to improve management strategies.